The role of the “Madeni Mura” Program in the context of the nation-building policy of Kazakhstan - Akhmetshina, G.U.; Mutalova, Dzh.S.; Zhakash, D.B.; Tulegenova, A.Zh. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
The article provides a comprehensive historical analysis of the history of the origin of the state program “cultural heritage” adopted by the Republic of Kazakhstan in 2004, the search for valuable documents, manuscripts, books, information related to the history of Kazakhstan from foreign archives and libraries, which became one of the most important areas within the framework of the program, their copying and import into the country, thereby enriching our spiritual and cultural heritage. This program was accepted by Kazakhstanis with great pleasure. Cultural heritage is a sign of a civilized society. The program consists of spiritual and moral values, as well as a comprehensive work taken to pass on the rich historical heritage of our people from generation to generation. The preservation of cultural heritage is of great importance for each of the peoples of the world. The program is aimed at developing and consolidating the national consciousness of Kazakhstanis. The purpose of writing the article by the authors is to determine the role of the Mindeni Mura program in considering the state-building policy of Kazakhstan over the years of independence, and to conduct a historical analysis.The relevance of the article lies in the fact that in the history of an independent country, the adoption of state programs in this direction is very important. Within the framework of the state program “Madeni Mura”, the rich historical heritage of our people was enriched with valuable relics from foreign archives. This program was the beginning of the subsequent programs “People in the Stream of History”, “Archive-2025”. The authors conclude that the study and introduction into scientific circulation of valuable documents brought to the country through the Madeni Mura Heritage program was a great step in the development of Kazakhstan's State-Building policy.
Қазақстанның мемлекет құру саясаты шеңберіндегі «Мәдени мұра» бағдарламасының рөлі
Роль программы «Мәдени мұра» в контексте политики национального строительства Казахстана
Keywords: “Cultural Heritage”; program; Republic of Kazakhstan; independence; archive; historical memory; cultural memory; national code; national culture; national construction; document; manuscript